SIDHARTA (Sistem Aplikasi Dharmayatra Nusantara) Sistem Informasi Berbasis Aplikasi Android, Digitalisasi Pelayanan Dharmayatra di Indonesia - Turipno Turipno; Trina Ristiani; Putri Anggraini Prastianingrum; Partono Nyanasuryanadi (Journal on Education, 2023)
Advances in science and technology accompanied by the rapid flow of globalization have had their own impact on human life, one of which is the development of technology in the field of communication. In the field of religion, it can be seen from significant changes, namely that Buddhism has begun to keep up with the times by using technology in carrying out religious activities such as dhamma lectures and online devotional service but there are still activities in Buddhism that have not been well coordinated, namely the dharmayatra ritual, therefore the researchers took the initiative to create a Dharmayatra Digitalization Service media in Indonesia called SIDHARTA (Dharmayatra Nusantara Application System). Dharmayatra activities from temple entrance tickets, travel routes, Dharmaytra packages, Dharmayatra guides, In developing this application researchers use the Development Life Circle Waterfall which has six steps The "SIDHARTA" application is an application that can be used by Buddhists in Indonesia. Through this application, it can facilitate the implementation of Dharmayatra ritual activities in Indonesia through the facilities available in the application.